2022
DOI: 10.18632/aging.204173
|View full text |Cite
|
Sign up to set email alerts
|

NOX4 promotes Kupffer cell inflammatory response via ROS-NLRP3 to aggravate liver inflammatory injury in acute liver injury

Abstract: Aim: This work aimed to investigate the mechanism of NOX4 in promoting Kupffer cells (KCs) activation and tissue inflammatory response in acute liver injury. Methods: Initially, the mouse KCs were cultured in vitro. Thereafter, the NOX4 overexpression plasmid was transfected into KCs to construct the overexpression cell line. Then, KCs inflammatory response was induced by LPS + Nigericin treatment. CCK-8 assay was performed to detect cell viability, flow cytometry (FCM) was conducted to measure cell apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Some ROS-producing oxidases, such as NADPH oxidase 4 and the 66-kDa isoform of Shc (p66Shc) promote the activation of liver Kupffer cells and HSCs by activating NLRP3, finally leading to liver inflammatory damage and fibrosis. 95 , 96 Pharmacological induction of HSC apoptosis is a feasible strategy to promote fibrosis regression, Li et al reported that forsythiaside A has anti-fibrosis potential by remolding extracellular matrix and improving oxidation stress to promote apoptosis of HSCs in vitro . Forsythiaside A down-regulates the NADPH oxidase 4/ROS signaling pathway to improve oxidation imbalance, decreases collagen-1 and α -SMA expression, and increases the ratio of pro-apoptotic Bax to anti-apoptotic Bcl-2.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Some ROS-producing oxidases, such as NADPH oxidase 4 and the 66-kDa isoform of Shc (p66Shc) promote the activation of liver Kupffer cells and HSCs by activating NLRP3, finally leading to liver inflammatory damage and fibrosis. 95 , 96 Pharmacological induction of HSC apoptosis is a feasible strategy to promote fibrosis regression, Li et al reported that forsythiaside A has anti-fibrosis potential by remolding extracellular matrix and improving oxidation stress to promote apoptosis of HSCs in vitro . Forsythiaside A down-regulates the NADPH oxidase 4/ROS signaling pathway to improve oxidation imbalance, decreases collagen-1 and α -SMA expression, and increases the ratio of pro-apoptotic Bax to anti-apoptotic Bcl-2.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The expression of NOX4 and related ROS generation was significantly increased during development of steatohepatitis in mice [156]. As recently reported by Zhai and colleagues in mouse model of liver injury, NOX4 activates the NLRP3 inflammasome and promotes inflammatory response in KCs by releasing of inflammatory factors, such as IL-6, IL-1β and TNF-α, speculating that NOX4 could be considered as a key factor in inflammatory response [157].…”
Section: Liver and Oxidative Stressmentioning
confidence: 66%
“…It has been demonstrated by different authors that there is a link between NOX4 activity and NLRP3 inflammasome activation. In Kupffer cells, NOX4-derived ROS promoted NLRP3 activation and significantly increased the expression of inflammasome components both in vitro and in vivo, aggravating liver inflammatory injury [ 27 ]. This mechanism has also been observed in various models of inflammation, such as acute pancreatitis [ 28 ], in high-glucose-induced endothelial dysfunction [ 29 ], in osteoarthritis [ 30 ], and in myocardial ischemia-reperfusion injury [ 31 ].…”
Section: Discussionmentioning
confidence: 99%